DNA methylation regulatory patterns and underlying pathways behind the co-pathogenesis of allergic rhinitis and chronic spontaneous urticaria - Yang, Zijiang; Wen, Puqiao; Chen, Jing; Kang, Jian; Xiang, Yaping; Ding, Shu; Gao, Lihua; Tong, Xiaoliang; Guo, Aiyuan (Frontiers in Immunology, 2023)
Background: Allergic rhinitis (AR) and chronic spontaneous urticaria (CSU) are often concurrent in patients. Changes in DNA methylation affect T cell biological processes, which may explain the occurrence and progression of comorbidity. However, downstream regulatory pathways of DNA methylation in two diseases and the underlying mechanisms have not been fully elucidated. Methods: The GSE50101, GSE72541, GSE50222 and OEP002482 were mined for the identification of differentially expressed genes (DEGs) or co-expressed genes and differentially methylated genes (DMGs) in AR and CSU patients. We applied GO analysis and consensus clustering to study the potential functions and signal pathways of selected genes in two diseases. GSVA and logistic regression analysis were used to find the regulatory pathway between DNA methylation and activation patterns of CD4+ T cells. Besides, we used the Illumina 850k chip to detect DNA methylation expression profiles and recognize the differentially methylated CpG positions (DMPs) on corresponding genes. Finally, we annotated the biological process of these genes using GO and KEGG pathway analysis. Result: The AR-related DEGs were found closely related to the differentiation and activation of CD4+ T cells. The DEGs or co-expressed genes of CD4+ T cells in AR and CSU patients were also clustered using GO and KEGG analysis and we got 57 co-regulatory pathways. Furthermore, logistic regression analysis showed that the regulation of cellular component size was closely related to the activation of CD4+ T cells regulated by DNA methylation. We got self-tested data using the Illumina 850k chip and identified 98 CpGs that were differentially methylated in patients. Finally, we mapped the DMPs to 15 genes and found that they were mainly enriched in the same CD4+T cell regulating pathway. Conclusion: Our study indicated that DNA methylation affected by pollen participated in the activation patterns of CD4 + T cells, providing a novel direction for the symptomatic treatment of the co-occurrence of AR and CSU.